Dynamics of a System of Rational Higher-Order Difference Equation. (20th May 2013) - Sroysang, Banyat
Abstract : We focus on a system of a rational m -order difference equation x n + 1 = ( x n - m + 1 ) / ( A + y n y n - 1 ⋯ y n - m + 1 ), y n + 1 = ( y n - m + 1 ) / ( B + x n x n - 1 ⋯ x n - m + 1 ), n = 0, 1, …, where A, B, x 0, x - 1, …, x - m + 1, y 0, y - 1, …, y - m + 1 ∈ ( 0, ∞ ) . We investigate the dynamical behavior of positive solution for the system.